Medical exploitation of Black people in America goes far beyond the cells stolen from Henrietta Lacks that produced modern day miracles - Hawkins, Deion Scott (The Conversation, 2023)
Medical exploitation is an often overlooked part of Black history and partly explains the mistrust that members of the Black community have for the medical industry.
United States of America
Keywords: 2023-08 August; Black American; Henrietta Lacks